2016
DOI: 10.1021/acsami.5b12819
|View full text |Cite
|
Sign up to set email alerts
|

Water-Mediated Photochemical Treatments for Low-Temperature Passivation of Metal-Oxide Thin-Film Transistors

Abstract: The low-temperature electrical passivation of an amorphous oxide semiconductor (AOS) thin-film transistor (TFT) is achieved by a deep ultraviolet (DUV) light irradiation-water treatment-DUV irradiation (DWD) method. The water treatment of the first DUV-annealed amorphous indium-gallium-zinc-oxide (a-IGZO) thin film is likely to induce the preferred adsorption of water molecules at the oxygen vacancies and leads to subsequent hydroxide formation in the bulk a-IGZO films. Although the water treatment initially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…The same group subsequently demonstrated that combining H 2 O mediation with DUV irradiation achieved better device performance than single DUV annealing due to a more complete M–O–M lattice formation and lower oxygen vacancy content in the oxide films …”
Section: Low Temperature Routes For Flexible and Printed High κ Oxidementioning
confidence: 99%
“…The same group subsequently demonstrated that combining H 2 O mediation with DUV irradiation achieved better device performance than single DUV annealing due to a more complete M–O–M lattice formation and lower oxygen vacancy content in the oxide films …”
Section: Low Temperature Routes For Flexible and Printed High κ Oxidementioning
confidence: 99%
“…However, in order to realize high definition, high frame-rate displays, and the relevant driving circuitry, the carrier mobility must be further improved while exhibiting good operational stability. For these reasons, various metal-oxide semiconductors [ 7 , 8 ], gate dielectrics [ 9 , 10 ], novel device structures [ 11 , 12 ], and post treatments [ 13 , 14 ] have been proposed to enhance the carrier mobility of these devices. Among the various approaches in achieving high mobility metal-oxide TFTs, using an ionic-type gate dielectric is a promising method of achieving both the high mobility and low voltage operation characteristics [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the proton irradiation, there was a clear decrease in the M‐O‐M lattice peak (529.70–530.97 eV) and significant increases in the M‐O vac ‐M (530.59–531.73 eV) and M‐O‐H (531.70–532.60 eV) peaks. As mentioned above, the high‐energy proton collision with the metal‐oxide lattice could induce the formation of oxygen vacancies, which remain as deep traps or shallow donor states, or which could subsequently generate hydroxides as a result of adsorbing water into the vacancies . The smaller oxygen vacancy generation energy within In 2 O 3 than in ZnO afforded the most significant reduction in the M‐O‐M peak with large M‐O vac ‐M and M‐O‐H peaks (Figure b) .…”
Section: Resultsmentioning
confidence: 92%